MANUFACTURING METHOD OF FISH BONE PASTE AND FOOD MADE USING THE SAME - MATSUSHITA MANABU; FUJITA YOSHIYUKI; SONODA KOJI; HIRAOKA YOSHINOBU (2014)
PROBLEM TO BE SOLVED: To provide a manufacturing method of fish bone paste and food made using the fish bone paste.SOLUTION: Fish bone (including fish meat) is softened by elevated temperature and pressure processing so that it can be eaten. The softened fish bone can be used as a food material by crushing, and masking the smell of fish. The "hamburger steak or cream croquette" manufactured from the food material of the fish bone has added amounts of calcium, collagen, EPA and DHA in comparison with products which do not contain fish bone. Besides, waste can be eliminated at the same time. 【課題】 魚骨ペーストの製造方法及びそれを利用した食品【解決手段】魚骨（魚肉を含む）は、高温高圧処理を行うと軟化し食することが出来ようになる。この軟化した魚骨を粉砕し、魚臭をマスキングすることによって食品素材として利用することが可能である。これら魚骨の食品素材から製造した「ハンバーグやクリームコロッケ」等は、魚骨を含まない製品と比較して、カルシウム、コラーゲン、ＥＰＡやＤＨＡを付加させることができる。また、同時に、廃棄物をなくすることも可能である。